GREENPEG exploration for pegmatite minerals to feed the energy transition: first steps towards the Green Stone Age - Müller, A (2023)
The GREENPEG project, which is funded by the European Commission Horizon 2020 Climate action, environment, resource efficiency and raw materials programme, aims to develop multimethod exploration toolsets for the identification of European, buried, small-scale (0.015 million m3 ) pegmatite ore deposits of the NbYF (NYF) and LiCsTa (LCT) chemical types. The project is being coordinated by the Natural History Museum of the University of Oslo and involves four exploration services/mining operators, one geological survey, one non-profit helix association of administration, industry and academia, two consulting companies and five academic institutions from eight European countries. The target raw materials are Li, high-purity quartz for silica and metallic Si, ceramic feldspar, rare earth elements, Ta, Be and Cs, which are naturally concentrated in granitic pegmatites. Silicon and Li are two of the most sought-after green technology metals as they are essential for photovoltaics and Li-ion batteries for electric cars, respectively. GREENPEG will change the focus of exploration strategies from large-volume towards small-volume, high-quality ores and overcome the lack of exploration technologies for pegmatite ore deposits by developing toolsets tailored to these ore types. This contribution focuses on the methods applied in the GREENPEG project and as such provides a potential pathway towards the Green Stone Age from the perspective of pegmatite-sourced minerals. (c) 2022 The Author(s).